Effects of oxyclozanide (Tremacid®) preparation against fascioliasis on clinical and haematological parameters in cattle of Bangladesh - Alam, Naim; Islam, Md; Howlader, Matiar; Lucky, Nasrin (International Journal of Biological Research, 2015)
The effects of Oxyclozanide (Tremacid®) on some clinical (body weight) and haematological parameters (TEC, Hb, PCV, ESR and TLC) were determined in this study. Among 55 cattle, 10 were selected, which were suffering from fascioliasis and divided randomly into two groups. Each group was consisting of five cattle. One was treated with Tremacid® @ (15 mg/kg body weight). Other was kept as an infected control group. Before trials with Tremacid® initial body weight, EPG of liver fluke and hematological parameters were examined. During the experimental period the faecal samples, clinical and hematological parameters were examined on 7th, 14th, 21st and 28th days for the determination of effects of Tremacid®. A significant reduction of EPG count was found on 7th, 14th, 21st and 28th day of Tremacid® (61.87%, 71.22%, 76.98% and 84.53%) in a treated cattle group. The EPG of an untreated control group was significantly (p<0.01) increased about 3.97%, 7.64%, 11.04% and 64.89% respectively. Total TEC was increased after treatment with Tremacid® and decreased in an untreated control group significantly (p<0.01), Likewise, after treatment with Tremacid® Hb content and PCV were increased, and ESR was decreased. Total leukocyte count (TLC) was decreased and the body weight was increased after Tremacid® treatment in the group A. On the other hand, Hb content PCV and body weight was decreased significantly (p<0.01) in the group B.